2022
DOI: 10.3389/fcimb.2022.873536
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Protein ChuP Connects Heme and Siderophore-Mediated Iron Acquisition Systems Required for Chromobacterium violaceum Virulence

Abstract: Chromobacterium violaceum is an environmental Gram-negative beta-proteobacterium that causes systemic infections in humans. C. violaceum uses siderophore-based iron acquisition systems to overcome the host-imposed iron limitation, but its capacity to use other iron sources is unknown. In this work, we characterized ChuPRSTUV as a heme utilization system employed by C. violaceum to explore an important iron reservoir in mammalian hosts, free heme and hemoproteins. We demonstrate that the chuPRSTUV genes compris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Genome analysis revealed the presence of multiple genetic elements within the chromosome, some associated with virulence. These included the type VI secretion system (cellular aggression mechanism [55]), flagella (mobility [56]), chromobacterium haem utilization and aerobactin operons (iron acquisition [57, 58]), as well as a P fimbriae operon (bacterial adhesion [59]). Unfortunately, there was insufficient DNA to perform long-read sequencing [60], and benefit from the improvements in draft assembly and resolving genomic complexity that this would have provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome analysis revealed the presence of multiple genetic elements within the chromosome, some associated with virulence. These included the type VI secretion system (cellular aggression mechanism [55]), flagella (mobility [56]), chromobacterium haem utilization and aerobactin operons (iron acquisition [57, 58]), as well as a P fimbriae operon (bacterial adhesion [59]). Unfortunately, there was insufficient DNA to perform long-read sequencing [60], and benefit from the improvements in draft assembly and resolving genomic complexity that this would have provided.…”
Section: Discussionmentioning
confidence: 99%
“…Genome analysis revealed the presence of multiple genetic elements within the chromosome, some associated with virulence. These included the type VI secretion system (cellular aggression mechanism [55]), flagella (mobility [56]), chromobacterium haem utilization and aerobactin operons (iron acquisition [57,58]), as well as a P fimbriae operon (bacterial adhesion [59]).…”
Section: Discussionmentioning
confidence: 99%
“…28 In another study, we have demonstrated that C. violaceum uses heme via the ChuPRSRTUV system, and that both siderophores and heme are important iron acquisition strategies during infection. 29 Further work by our group has shown that Fur protects C. violaceum against iron overload and oxidative stress. Also, Fur represses genes related to iron homeostasis and controls virulence in this bacterium.…”
Section: Introductionmentioning
confidence: 97%
“…We propose that these siderophores are assembled by the nonribosomal peptide synthetases (NRPS) CbaF and VbaF from the 2,3-DHBA precursor and imported by the TonB-dependent receptors CbuA and VbuA, respectively ( 28 ). In another study, we have demonstrated that C. violaceum uses heme via the ChuPRSTUV system, and that both siderophores and heme are important iron acquisition strategies during infection ( 29 ). Further work by our group has shown that Fur protects C. violaceum against iron overload and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%